The impact of elexacaftor/tezacaftor/ivacaftor on cystic fibrosis health-related quality of life and decision-making about daily treatment regimens: a mixed methods exploratory study - Melissa Basile; Jennifer Polo; Katherine Henthorne; Joan DeCelie-Germana; Susan Galvin; Janice Wang (SAGE Publishing, 2024)
Background: Elexacaftor/tezacaftor/ivacaftor (ETI) has reduced many symptoms of cystic fibrosis (CF). Objectives: We sought to identify the impact of ETI on both symptoms and treatment decisions among adults with CF. Design: Participants were enrolled in a cross-sectional study. Surveys were sent via a RedCap link. Semistructured interviews were administered remotely via Microsoft Teams. Interviews were audio recorded and professionally transcribed. Methods: We assessed Cystic Fibrosis Questionnaire-Revised (CFQ-R) subscales for physical, respiratory, emotion, and treatment, and analyzed semistructured interviews covering CF treatment regimens and daily living. Quantitative and qualitative results were analyzed separately and via a mixed-methods convergence coding matrix. Results: Twenty-four adults with CF taking ETI were included. CFQ-R subscale scores (mean scores/standard deviation) were physical (82.1/22.8), respiratory (83.7/11.2), emotion (65.3/14.2), and treatment (57.5/20.1). Three themes about decision-making for non-ETI-treatments emerged: (1) How I'm feeling, (2) Not noticing a difference, and (3) Uncertainty about long-term impact of modifying treatment regimens, and we found participants weighed each of these factors in their treatment decisions. Key findings from mixed-methods analysis show that among individuals experiencing higher CFQ-R scores for physical and respiratory compared to emotion and treatment, there were statements indicating that while those participants were experiencing better physical health, many continued their burdensome treatment regimens. Conclusion: With little long-term data on the impact of reducing non-ETI treatments, participants weighed how they were feeling, treatment efficacy beliefs, and risk tolerance when making treatment decisions.